The correlations between the determinants of women's health during pregnancy to the incidence of stunting - Nur Lathifah; Linda Kusumawati; Adriana Palimbo; Fathonatun Jannah (Ananda - Health & Education Foundation, 2024)
Background: WHO's target of reducing stunting below 20% has not been achieved in Indonesia, especially in Banjar Regency, with a prevalence of 33.45%. Lok Buntar village became the locus of stunting, where 38.7% of the 116 children under five were stunted, with several determining factors including age at pregnancy, a woman's height, birth spacing, nutritional status, and anemia. Objective: This study aims to determine the relation between determinants of maternal health during pregnancy and the incidence of stunting in Lok Buntar Village, Banjar Regency. Method: This type of observational analytic research with a retrospective design case-control approach. The total sample of 90 pregnant women, consisting of 45 cases and 45 controls, was taken by random sampling technique. Secondary data collection instruments used were checklists, cohorts of mothers and toddlers, and MCH books. Results: Findings show that the age of women during pregnancy is 84.0% at risk between 20 to 35 years, p-value 0.000. The spacing of births within two years was 70.4%, while the spacing of more than two years was 41.3%, with a p-value of 0.021. Respondents who have a height below 150 cm are 68.6%, with a p-value of 0.009. The nutritional status of pregnant women experiencing caloric energy deficiency is 84.2%, with a p-value of 0.002. Meanwhile, anemia and the risk of stunting were 89.7%, with a p-value of 0.000. Conclusion: The determinants of women's health during pregnancy have significant correlations with the incidence of stunting.